Modular assembly of transposable element arrays by microsatellite targeting in the guayule and rice genomes - Valdés Franco, José A.; Wang, Yi; Huo, Naxin; Ponciano, Grisel; Colvin, Howard A.; McMahan, Colleen M.; Gu, Yong Q.; Belknap, William R. (BioMed Central, 2018)
Abstract Background: Guayule (Parthenium argentatum A. Gray) is a rubber-producing desert shrub native to Mexico and the United States. Guayule represents an alternative to Hevea brasiliensis as a source for commercial natural rubber. The efficient application of modern molecular/genetic tools to guayule improvement requires characterization of its genome. Results: The 1.6 Gb guayule genome was sequenced, assembled and annotated. The final 1.5 Gb assembly, while fragmented (N50 =22 kb), maps >95% of the shotgun reads and is essentially complete. Approximately 40,000 transcribed, protein encoding genes were annotated on the assembly. Further characterization of this genome revealed 15 families of small, microsatellite-associated, transposable elements (TEs) with unexpected chromosomal distribution profiles. These SaTar (Satellite Targeted) elements, which are non-autonomous Mu-like elements (MULEs), were frequently observed in multimeric linear arrays of unrelated individual elements within which no individual element is interrupted by another. This uniformly non-nested TE multimer architecture has not been previously described in either eukaryotic or prokaryotic genomes. Five families of similarly distributed non-autonomous MULEs (microsatellite associated, modularly assembled) were characterized in the rice genome. Families of TEs with similar structures and distribution profiles were identified in sorghum and citrus. Conclusion: The sequencing and assembly of the guayule genome provides a foundation for application of current crop improvement technologies to this plant. In addition, characterization of this genome revealed SaTar elements with distribution profiles unique among TEs. Satar targeting appears based on an alternative MULE recombination mechanism with the potential to impact gene evolution. Keywords: Natural rubber, Genome, Assembly, Annotation, Class II transposable element, Non-autonomous, Transposon